2000
DOI: 10.1002/1521-3765(20000602)6:11<1980::aid-chem1980>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Activity Enhancement by the Support in the Hydrogenation of C=C Bonds over Polymer-Supported Palladium Catalysts

Abstract: Four synthetic ion-exchange resins (AH, BH, CH, DH) of different hydrophilic/hydrophobic properties were used as supports for heterogeneous palladium catalysts (A, B, C, D). The resins contained styrene (STY) and 2-(methacryloxy)ethylsulfonic acid (MESA) as the comonomers. Either divinylbenzene (DVB: CH, DH resins) or N,N'-methylenebisacrylamide (MBAA: AH, BH resins) were used as the cross-linker. AH contained also N,N-dimethylacrylamide (DMAA) as the third comonomer. The catalysts (Pd 0.25-0.45% w/w) were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 2 publications
1
14
0
2
Order By: Relevance
“…To compare supports with different surface hydrophobicities, we also used a 1,4‐(bistriethoxysilyl)benzene derived periodic mesoporous organosilica support (PMO). However, the catalytic results confirmed that the hydrophobicity of the support surface should not play an important role in the hydrogenation reaction according to findings of Zecca et al 19…”
Section: Resultssupporting
confidence: 73%
“…To compare supports with different surface hydrophobicities, we also used a 1,4‐(bistriethoxysilyl)benzene derived periodic mesoporous organosilica support (PMO). However, the catalytic results confirmed that the hydrophobicity of the support surface should not play an important role in the hydrogenation reaction according to findings of Zecca et al 19…”
Section: Resultssupporting
confidence: 73%
“…PdNP@resins are effective catalysts, including as bifunctional catalysts [68,69], for a variety of processes and are at the core of the large scale manufacture of methyl isobutyl ketone and methyl-tert-butyl ether [70,71]. Common precursors employed for the PdNP@resin synthesis are either [Pd(NH3)4] 2+ or Pd(CH3CO2)2, for cation exchange resins, and PdCl4 2-, for anion exchange resins, which require high temperature treatment or large excesses of sodium borohydride for their conversion to Pd metal [72,73].…”
Section: Pdnp@resinmentioning
confidence: 99%
“…[ 12] Ihm and co‐workers reported the hydrogenation of olefinic double bonds by using gel‐like and macroporous polymer‐supported palladium(II) complexes13a while Zecca et al. used the ion‐exchange resins‐supported palladium catalyst for the same reaction 13b. Manorama and co‐workers reported the Pd immobilized on amine‐terminated ferrite nanoparticles for hydrogenation of aromatic nitro and azide compounds 14.…”
Section: Introductionmentioning
confidence: 99%